Study of the Anatomical Features of the Offending Arteries Involved in Glossopharyngeal Neuralgia. Issue 3 (20th January 2020) - Inoue, Kohei; Matsushima, Toshio; Ohara, Shinji; Masuoka, Jun; Abe, Tatsuya
Abstract: BACKGROUND: The anatomic features of the posterior inferior cerebellar arteries (PICAs) and the anterior inferior cerebellar arteries (AICAs) as offending arteries involved in glossopharyngeal neuralgia (GPN) are important to dictate the best surgical approach. OBJECTIVE: To study and classify the anatomic features of the offending arteries. METHODS: All clinical data and surgical videos from 18 GPN cases that were surgically treated during the past 10 yr were retrospectively reviewed. RESULTS: Among these 18 patients, the offending arteries involved were the PICA in 12 (66.7%), AICA in 4 (22.2%), and both PICA and AICA in 2 (11.1%). The PICA were then classified into the following groups based on their anatomic features: type I: the PICA formed an upward loop at the level of the glossopharyngeal nerve and passed between the glossopharyngeal and vestibulocochlear nerves; type II: the PICA formed an upward loop at the level of the glossopharyngeal nerve and passed between the glossopharyngeal and vagus nerves or between the rootlets of the vagus nerve; and type III: the PICA passed between the glossopharyngeal and vestibulocochlear nerves without forming a loop. The AICA had only one running pattern. CONCLUSION: The offending arteries involved in GPN, mainly the PICA and/or AICA, were classified into 4 different types based on their anatomic features.